PEMANFAATAN BUAH DAN SAYUR SEBAGAI SUMBER ENERGI ALTERNATIF PEMBUATAN BIO- BATERAI DI SDN PAREREJO 01 - Ira Ayu Safitri; Riyanto Riyanto; Dian Fitri Argarini (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2023)
Batteries are a source of electrical energy that is widely used in everyday life. Batteries contain heavy metals which are not environmentally friendly and therefore have the potential to cause environmental pollution. One solution that can be done, namely using fruit and vegetables as alternative energy, is still not done optimally. Alternative energy is environmentally friendly energy obtained from materials that have never been used before. The fruits and vegetables used in practice are as follows: potatoes, tomatoes, and limes. The methods used in this service activity are; the practice of creating electrical circuits directly using fruit and vegetables as an energy source. From the results of the practice it can be concluded that fruit and vegetables can be used as an alternative energy source for bio-batteries.